Challenges and directions in implementing translanguaging pedagogy for low achieving students. Issue 3 (2nd October 2019) - Vaish, Viniti
ABSTRACT: What are the challenges faced by a research team in implementing translanguaging pedagogy in a multilingual classroom? What implications does this research project have for researchers in other geographies and other languages? This paper answers these questions on the basis of 7 English reading classes and interviews of teachers and students recorded in August 2012 in School W, located in an area where most of the children come from Malay dominant homes. School W had consented to being a pilot school in order to improve vocabulary, grammar and comprehension in English by using the Mother Tongues of the children in the Learning Support Program. Specifically the paper focuses on the challenge of teaching a class where, though most children come from Malay speaking homes, some speak Chinese or Tamil at home. The main challenges for the research team were 'superdiversity' of language backgrounds in the classroom and negative attitudes towards Mother Tongue amongst the children. The paper ends with decisions made by the researchers based on this pilot project which have implications for teachers, policy makers and advocates of translanguaging pedagogy in diverse contexts.